Persistant left superior vena cava – the value of an agitated saline contrast study - Moses, Jane; Kyriakakis, Charles; Weich, Hellmuth; Rossouw, Pieter; Herbst, Philip; Doubell, Anton (SA Heart Journal, 2017)
A persistant left superior vena cava (PLSVC) draining to the coronary sinus (CS) is the most common venous anomaly of the thorax, affecting approximately 0.5% - 2% of the general population, and is present in up to 10% of patients with other congenital cardiac anomalies.(1) The embryological development of the thoracic venous system is complex and subject to significant variation. Usually, most of the left cardinal system involutes, leaving only the coronary sinus, which drains the cardiac veins, and the ligament of Marshall (a remnant of the left superior vena cava).(2) The presence of a PLSVC is usually an incidental finding at either echocardiography, cardiac catheterisation or device implantation.(1) The typical echocardiographic findings are that of a dilated CS, which can be appreciated on the parasternal long axis view, the parasternal short axis at mitral valve level, the apical 2 chamber view and a modified apical four chamber view scanning down to visualise the CS (Figure 1). A contrast study with agitated saline (“bubble study”) done via the left brachial vein will demonstrate the dilated CS draining into the right atrium (Figure 2).